Analysis of Ionospheric and Geomagnetic Response to the 2020 Patagonian Solar Eclipse - Meza, Amalia; Eylenstein, Bernardo; Natali, María Paula; Bosch, Guillermo; Moirano, Juan; Chalar, Elfriede (Frontiers in Astronomy and Space Sciences, 2021)
Total solar eclipses are unique opportunities to study how the ionospheric and external geomagnetic field responds to fast changes in the ionizing flux as the moon's shadow travels through its path over the ionosphere at an average speed of 3000 km/h. In this contribution, we describe our observing campaign in which we set up GNSS and geomagnetic stations at the city of Valcheta, Río Negro, Argentina (which was located right under the path of totality). We also describe the results obtained from the analysis of the combination of on-site data together with publicly available observations from geodetic and geomagnetic observatories. The large span in latitude of our data allowed us to analyze the different magnitudes of the drop in vertical total electron content ($Δ$VTEC) with varying occultation percentages. We found an expected reduction in this drop as we move away from totality path but we also detected a new increment in Delta_VTEC as we got closer to Earth's Magnetic Equator. We also compared our observations of the geomagnetic field variations with predictions that were based on the Ashour-Chapman model and we find an overall good agreement, although a ~ 20 min delay with the eclipse maximum is evident beyond observing uncertainties. This suggests the presence of processes that delay the response of the lower ionosphere to the loss of the photoionization flux.